Development of Testing Standardization Regulation of the OLT XG-PON Equipments to Support Broadband Access in Indonesia - Muhammad Imam Nashiruddin; Nomarhinta Solihah (BBPSDMP KOMINFO MAKASSAR, 2020)
This study aims to provide a reference to the technical specifications of the Optical Line Termination (OLT) XG-PON equipment for improving standardization regulations (Perdirjen Postel No. 257 of 2008). The technical specifications tested in this study are the nominal rate capability, wavelength range, and jumbo frame of the OLT XG-PON equipment. The research acquired a reference to the nominal rate using FEC is 8.5 Gbps downstream direction, and 2.5 Gbps upstream direction, upstream wavelength range is 1260-1280 nm and downstream is 1575-1581 nm, and jumbo frame capability is 2000 Bytes.